Large Parosteal Lipoma without Periosteal Changes. Issue 1 (January 2015) - Aoki, Shimpo; Kiyosawa, Tomoharu; Nakayama, Eiko; Inada, Chiaki; Takabayashi, Yuki; Sumi, Yuki; Doumoto, Takashi; Aizawa, Tetsushi; Azuma, Ryuichi
<x xml:space="preserve">Abstract</x> Summary: Parosteal lipoma is a rare tumor, accounting for approximately 0.3% of all lipomas. Bony lesions are often found in patients with this tumor (59.2%), making the differential diagnosis of malignant tumors important. Our case was a 64-year-old male patient who complained of a 25 × 15-cm mass on his right thigh that had grown rapidly over a 2-month period. On magnetic resonance imaging, a high-intensity lesion was observed on the surface of the femur beneath the vastus medialis muscle on T1 and T2 images, with low intensity on a T1 fat suppression image. No significant bony changes were detected. During total tumor resection, the tumor was found on the femur with tight continuity, with tiny areas of spiculation palpable on the bone surface. The exact tumor size was 18 × 13 × 6 cm. The pathological diagnosis was lipoma, the same result as in the former open biopsy. This case was the largest parosteal lipoma of the femur reported without periosteal changes. In cases of deep parosteal lipomas, the detection of rapidly progressive and growing pseudotumors with ossification or chondromatous changes implies malignancy. A preoperative biopsy is mandatory and must be followed by careful planning and preparation for handling in malignant cases. Plastic surgeons should therefore keep the diagnosis of parosteal lipoma in mind to provide appropriate (not too much or too little) surgical treatment.